Industrial Concentration as Shown by the Census - Ripley, William Z. (Quarterly Journal of Economics, 1907)
Industrial Concentration as Shown by the Census Get access William Z. Ripley William Z. Ripley Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 21, Issue 4, August 1907, Pages 651–658, https://doi.org/10.2307/1883592 Published: 01 August 1907